PENGARUH STRES KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Survei pada Karyawan PT Indaco Warna Dunia Karanganyar) - Alwi Suddin, Kristianto Utomo, Marjam Desma Rahadhini & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
PT Indaco Warna Dunia Karanganyar in conducting its operational activitiestrying to improve employee performance. Factors affecting the performance ofemployees is the stress of work, compensation and job satisfaction. The purpose ofresearch is to analyze the significance of the effect of work stress on job satisfaction andcompensation to the employees of PT Indaco Warna Dunia Karanganyar, analyze thesignificance of the effect of work stress, compensation and job satisfaction on theperformance of employees of PT Indaco Warna Dunia Karanganyar, analyze jobsatisfaction in mediating the effects of work stress and compensation to employeesperformance of PT Indaco Warna Dunia Karanganyar. This study uses survey method,the type of data used quantitative and qualitative data, the data source used primarydata and secondary data. The population in this study were all employees of PT IndacoWarna Dunia Karanganyar as many as 344 employees. The number of samples in thisstudy as many as 69 people, the sampling technique using proportional randomsampling. Data collection methods are used: questionnaires and documentation. Dataanalysis technique used to test the validity, reliability test, classic assumption test, andpath analysis. In conclusion: there is a significant effect of work stress on jobsatisfaction, there was a significant effect of compensation on employee job satisfaction,there was a significant effect of work stress on employee performance, there was asignificant effect of compensation to employee performance, there is a significantinfluence job satisfaction the performance of employees, there is an indirect effect ofwork stress on employee performance mediated by job satisfaction, there is the indirecteffect of compensation to employee performance mediated job satisfaction. Suggestionsin this research are: Chairman of PT Indaco Warna Dunia Karanganyar in an effort toimprove employee performance should evaluate its policies before a potentially stressfulfor employees, in particular by reducing the activity outside the duties andresponsibilities of employees, and conduct recreational activities for all employees aswell as continue to maintain and even improve employee satisfaction so the employee'sperformance may continue to rise.Keywords: job stress, compensation, job satisfaction, employee performance